2020
DOI: 10.1038/s41598-020-70081-3
|View full text |Cite
|
Sign up to set email alerts
|

Best period to replace or change plastic stents with self-expandable metallic stents using multivariate competing risk regression analysis

Abstract: In endoscopic biliary drainage (EBD) for various benign and malignant biliary disorders, the appropriate timing to replace or change a plastic stent (PS) with a self-expandable metallic stent (SEMS) remains unclear. This study aimed to define the best period to replace or change a PS with a SEMS. Between January 1, 2012, and December 31, 2018, 1,887 consecutive EBD procedures, including 170 SEMS placements, were retrospectively identified. The period to recurrent biliary obstruction (PRBO) was estimated and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…28,29 However, it is difficult to predict the actual period to stent obstruction. 27 Therefore, our result that more patients underwent scheduled sequential procedure in 3 months after the index procedure without PS occlusion is notable. It is suggested that ID-RFA is beneficial by preventing premature stent occlusion before scheduled exchange.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…28,29 However, it is difficult to predict the actual period to stent obstruction. 27 Therefore, our result that more patients underwent scheduled sequential procedure in 3 months after the index procedure without PS occlusion is notable. It is suggested that ID-RFA is beneficial by preventing premature stent occlusion before scheduled exchange.…”
Section: Discussionmentioning
confidence: 67%
“…To avoid this, guidelines state scheduled stent exchange could be a strategy for better outcomes 28,29 . However, it is difficult to predict the actual period to stent obstruction 27 . Therefore, our result that more patients underwent scheduled sequential procedure in 3 months after the index procedure without PS occlusion is notable.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Among 26 NAT patients with a plastic stent dysfunction, 16 (62%) patients received a SEMS during the first repeat ERCP. The decision on changing the stent type from plastic stent to SEMS was made based on guidelines and studies supporting the replacement of plastic stents to SEMSs on the basis of the underlying disease [ 6 , 17 ]. Median time from primary biliary drainage to first repeat ERCP among NAT patients with plastic stents was 77 days (range 9–263 days).…”
Section: Resultsmentioning
confidence: 99%
“…Patient death was treated as a censor, and differences were evaluated using the log‐rank test for the Kaplan–Meier analysis (Figure 2a). The Fine and Gray model, based on a subdistribution hazard (SHR) model, was used for the competing‐risks regression (CRR) 4,26,28 . To include death in this model's informative censoring for potential RBO, death without RBO was treated as a competing risk.…”
Section: Methodsmentioning
confidence: 99%